Assessing the irradiance levels of phototherapy devices in Jos, north central, Nigeria - Ofakunrin, Akinyemi O. D.; Diala, Udochukwu M.; Toma, Bose O.; Shwe, David D.; Gidado, Sanusi; Afolaranmi, Tolulope O.; Bode-Thomas, Fidelia (International Journal of Research in Medical Sciences, 2018)
Background: Neonatal jaundice (NNJ) remains a major cause of neonatal morbidity and mortality in Nigeria with significant contribution to the global figures. Effective phototherapy can reduce the complications associated with NNJ. The effectiveness of a phototherapy device (PD) depends mainly on the emitted irradiance of the device. We, therefore, assessed the irradiance of the PDs in Jos, North Central Nigeria in order to determine the effectiveness of the devices and to highlight the need for routine assessment of irradiance levels of PDs in low-middle income settings. Methods: This was a cross- sectional study involving 14 hospitals with a total of 38 functional PDs comprising of 25 (65.8%) locally fabricated, eight (21.0%) light- emitting diode (LED) and five (13.2%) conventional patented devices. The irradiance was measured using the BiliBlanket® light meter II. Results: The irradiance of the PDs ranged from 2 to 102μW/cm2/nm with a median value of 10.6 (IQR 6-18μW/cm2/nm). Sixteen devices (42.1%) had a suboptimal irradiance (<10μW/cm2/nm); while only five (13.2%) provided irradiance at the intensive level (≥30μW/cm2/nm). The mean distance between the babies and phototherapy lights was 35.1±12.7cm (range 15-70cm). Conclusions: A significant proportion of the PDs in Jos delivered suboptimal irradiance which could reduce the effectiveness of the phototherapy. The irradiance of PDs needs to be assessed regularly and measures should be instituted to improve the irradiance to the optimum level in order to reduce the burden of kernicterus.